Ghrelin projection from the lateral hypothalamus area to the dorsal vagal complex and its regulation of gastric motility in cisplatin-treated rats. (December 2017) - Gong, Yanling; Liu, Yang; Guo, Yaoyao; Su, Manqing; Zhong, Yifan; Xu, Luo; Guo, Feifei; Gao, Shengli
Abstract: Objective: To investigate ghrelin projection from the lateral hypothalamus area (LHA) to the dorsal vagal complex (DVC) and its regulation of gastric motility in cisplatin-treated rats. Materials and methods: In the present study, the protein and mRNA expression of ghrelin and its receptor GHSR-1a were measured by Western blot and PCR, respectively. The ghrelin fiber projections arising from the LHA and projecting to the DVC were investigated by retrograde tracing combined with fluoro-immunohistochemical staining. The effects of ghrelin in the DVC, electrical stimulation of the LHA, and electrical lesion of the DVC on gastric motility were measured in cisplatin-treated rats. Results: Ghrelin fibers originating in the LHA projected to the DVC. The protein and mRNA expression of GHSR-1a was greater in cisplatin-treated rats than in saline-treated rats. Conversely, the expression of ghrelin in the LHA and DVC was reduced in cisplatin-treated rats. Cisplatin treatment also reduced gastric contractions. Ghrelin administrated into the DVC significantly promoted gastric motility, an effect completely blocked by treatment with the ghrelin receptor antagonist [D-Lys-3]-GHRP-6. In addition, electrical stimulation of the LHA promoted gastric motility, though this effect was much weaker in cisplatin-treated rats than in control rats. The excitatory effect of electrical stimulation of the LHA on gastric motility was partially blocked by pretreatment of the DVC with [D-Lys-3]-GHRP-6. Electrical lesion of the DVC diminished the excitatory effect that was induced by electrical stimulation of the LHA. Conclusions: DVC, especially AP, may have a role for gastric contraction induced by the stimulation of the LHA. This regulation on gastric motility was weaker in cisplatin-treated rats than in saline-treated rats, possibly due to reduced ghrelin expression in the LHA and ghrelin projection from the LHA to the DVC. Highlights: Ghrelin fibers originating in the LHA projects to the DVC in rats which is destroyed by cisplatin. Cisplatin decreases expression of ghrelin and increases expression of GHSR-1a. Ghrelin in DVC and electrical stimulating of the LHA promotes gastric motility in cisplatin-treated rats.